Impact of COVID-19 on agricultural markets: Assessing the roles of commodity characteristics, disease caseload and market reforms - Varshney, Deepak; Roy, Devesh; Meenakshi, J. V. (Springer, 2020)
This paper assesses the impact of the spread of COVID-19 and the lockdown on wholesale prices and quantities traded in agricultural markets. We compare whether these impacts differ across non-perishable (wheat) and perishable commodities (tomato and onion), and the extent to which any adverse impacts are mitigated by the adoption of a greater number of agricultural market reform measures. We use a granular data set comprising daily observations for 3 months from nearly 1000 markets across five states and use a double- and triple- difference estimation strategy. Expectedly, our results differ by type of commodity and period of analysis. While all prices spiked initially in April, they recovered relatively quickly, underscoring the importance of time duration for analysis. Wheat prices were anchored in large part by the minimum support price, while tomato prices were lower in some months. Supply constraints began easing in May with greater market arrivals perhaps reflecting distress sales. Market reform measures did help in insulating farmers from lower prices, but these effects are salient for the perishable goods, and not so much for wheat where the government remained the dominant market player. Taken together, these results point to considerable resilience in agricultural markets in dealing with the COVID-19 shock, buffered by adequate policy support.